The OCB Roles as a Mediator Self-Actualization, Psychological Well Being, and Work Environment on Health Worker Performance: Study during COVID-19 Pandemic in Indonesia - Wenda Anthonie; Bernhard Tewal; Olivia S Nelwan; Greis M. Sendow; Victor P.K. Lengkong (Pusat Riset dan Inovasi Nasional, 2022)
This study focuses on determining the role of organizational citizenship behavior or OCB as a mediator the relationship between self-actualization, psychological well-being, and the work environment on the performance of health workers with studies during the COVID-19 pandemic in Indonesia. Data were collected from 89 nurses who work in hospitals owned by police institutions in Manado City, Indonesia. Respondents were surveyed directly about their perceptions related to the research topic. The results showed that OCB acts as a mediator between self-actualization, psychological well-being, and the work environment on the performance of health workers. Directly only the work environment has an insignificant effect on the performance of health workers, while other variables indicate a positive and significant relationship. These findings contribute to hospital management and other relevant institutions, as well as human resource research during the COVID-19 pandemic. Some of the limitations of this study are described at the end of this article.